Depression and Anxiety in Patients Treated in the Coronary Intensive Care Unit - Gömleksiz, Mehtap; Pirincci, Edibe; Yılmaz, Sema; Oguzoncul, Ayse Ferdane; Yakar, Burkay (My University, 2024)
Objective: Ensuring the survival of patients has been accepted as a successful outcome in recent years, but it is known that patients are exposed to negative emotional consequences during their stay in intensive care units. The aim of this study was to investigate the depression and anxiety status of patients hospitalized in the coronary intensive care unit and the affecting factors. Material and Method: The population of the cross-sectional and descriptive study consists of 230 patients who were hospitalized in the Coronary Intensive Care Unit of University Hospital in May-July 2019. Study data were obtained by using a sociodemographic questionnaire and Hospital Anxiety and Depression (HAD) scale. In statistical evaluations, t test, one-way analysis of variance tests were applied. Results: The mean age of the patients included in the study was 65,55±12,73, and 42.2% of them (n =97) were female and 57.8% (n =133) were male. The mean score of the anxiety subscale was 8,20±3,56, and the mean of the depression subscale was 9,32±4,26. The mean score of anxiety (p <0,001) and depression (p <0,05) in female patients was found to be higher than male patients. It was determined that patients over 60 years of age, whose spouses died or were divorced, scored higher in the depression subscale (p <0,05). Conclusion: One third of the patients under treatment in the coronary intensive care unit are affected by anxiety, and a very large portion of them are affected by depression. Contrary to expectations, it was found that depression affects the intensive care patient population more. More research is needed on anxiety and depression rates and affecting factors in intensive care patients.
Keywords: Depression; Anxiety; Intensive Care; Coroner